Haemodynamics and vasopressor support during prolonged targeted temperature management for 48 hours after out-of-hospital cardiac arrest: a post hoc substudy of a randomised clinical trial. Issue 2 (17th June 2020) - Grand, Johannes; Hassager, Christian; Skrifvars, Markus B; Tiainen, Marjaana; Grejs, Anders M; Jeppesen, Anni Nørgaard; Duez, Christophe Henri Valdemar; Rasmussen, Bodil S; Laitio, Timo; Nee, Jens; Taccone, FabioSilvio; Søreide, Eldar; et al.
Abstract: Background: Comatose patients admitted after out-of-hospital cardiac arrest frequently experience haemodynamic instability and anoxic brain injury. Targeted temperature management is used for neuroprotection; however, targeted temperature management also affects patients' haemodynamic status. This study assessed the haemodynamic status of out-of-hospital cardiac arrest survivors during prolonged (48 hours) targeted temperature management at 33°C. Methods: Analysis of haemodynamic and vasopressor data from 311 patients included in a randomised, clinical trial conducted in 10 European hospitals (the TTH48 trial). Patients were randomly allocated to targeted temperature management at 33°C for 24 (TTM24) or 48 (TTM48) hours. Vasopressor and haemodynamic data were reported hourly for 72 hours after admission. Vasopressor load was calculated as norepinephrine (µg/kg/min) plus dopamine(µg/kg/min/100) plus epinephrine (µg/kg/min). Results: After 24 hours, mean arterial pressure (mean±SD) was 74±9 versus 75±9 mmHg ( P =0.19), heart rate was 57±16 and 55±14 beats/min ( P =0.18), vasopressor load was 0.06 (0.03–0.15) versus 0.08 (0.03–0.15) µg/kg/min ( P =0.22) for the TTM24 and TTM48 groups, respectively. From 24 to 48 hours, there was no difference in mean arterial pressure ( P group =0.32) or lactate ( P group =0.20), while heart rate was significantly lower (average difference 5 (95% confidence interval 2–8) beats/min, P group <0.0001) and vasopressor load was significantly higher in the TTM48 group ( P group =0.005). In a univariate Cox regression model, high vasopressor load was associated with mortality in univariate analysis (hazard ratio 1.59 (1.05–2.42) P =0.03), but not in multivariate analysis (hazard ratio 0.77 (0.46–1.29) P =0.33). Conclusions: In this study, prolonged targeted temperature management at 33°C for 48 hours was associated with higher vasopressor requirement but no sign of any detrimental haemodynamic effects.